Programa a leer textos para desarrollar los niveles de comprensión lectora en los estudiantes de tercer grado de Educación Primaria – Trujillo, 2019 - Chup Perez, Gianella Alexandra (2022)
This research work is part of the educational sector and its main objective is to determine the effectiveness of the Program called ´To read texts´ to improve reading comprehension levels. The research corresponds to the quantitative research approach with a quasi experimental design, taking as a non-probabilistic sample or intact groups third grade primary school students, divided into a control group and an experimental group, to whom the pre-test and post-test were applied. The instrument used is a reading comprehension test, which consists of a narrative, descriptive, instructive and informative text, which was designed with the three levels of reading comprehension as dimensions. The findings have shown a significant difference in means between both groups, the control group and the experimental group, with the value p = 0.000 <α (0.05) in the general result of reading comprehension and in its respective dimensions: literal, inferential and critical. In conclusion, the ´To read texts´ program does significantly develop the reading comprehension of the students of the third grade of Primary Education of the educational institution N° 80002 ´Antonio Torres Araujo´ - Trujillo 2019.